Immune response to allogeneic equine mesenchymal stromal cells - J. Lacy Kamm (BMC, 2021)
Abstract Background Mesenchymal stromal cells (MSCs) are believed to be hypoimmunogeneic with potential use for allogeneic administration. Methods Bone marrow was harvested from Connemara (n = 1), Standardbred (n = 6), and Thoroughbred (n = 3) horses. MSCs were grouped by their level of expression of major histocompatibility factor II (MHC II). MSCs were then sub-grouped by those MSCs derived from universal blood donor horses. MSCs were isolated and cultured using media containing fetal bovine serum until adequate numbers were acquired. The MSCs were cultured in xenogen-free media for 48 h prior to use and during all assays. Autologous and allogeneic MSCs were then directly co-cultured with responder leukocytes from the Connemara horse in varying concentrations of MSCs to leukocytes (1:1, 1:10, and 1:100). MSCs were also cultured with complement present and heat-inactivated complement to determine whether complement alone would decrease MSC viability. MSCs underwent haplotyping of their equine leukocyte antigen (ELA) to determine whether the MHC factors were matched or mismatched between the donor MSCs and the responder leukocytes. Results All allogeneic MSCs were found to be ELA mismatched with the responder leukocytes. MHC II-low and universal blood donor MSCs caused no peripheral blood mononuclear cell (PBMC) proliferation, no increase in B cells, and no activation of CD8 lymphocytes. Universal blood donor MSCs stimulated a significant increase in the number of T regulatory cells. Neutrophil interaction with MSCs showed that universal blood donor and MHC II-high allogeneic MSCs at the 6 h time point in co-culture caused greater neutrophil activation than the other co-culture groups. Complement-mediated cytotoxicity did not consistently cause MSC death in cultures with active complement as compared to those with inactivated complement. Gene expression assays revealed that the universal blood donor group and the MHC II-low MSCs were more metabolically active both in the anabolic and catabolic gene categories when cultured with allogeneic lymphocytes as compared to the other co-cultures. These upregulated genes included CD59, FGF-2, HGF, IDO, IL-10, IL-RA, IL-2, SOX2, TGF-β1, ADAMSTS-4, ADAMSTS-5, CCL2, CXCLB/IL-8, IFNγ, IL-1β, and TNFα. Conclusions MHC II-low MSCs are the most appropriate type of allogeneic MSC to prevent activation of the innate and cell-mediated component of the adaptive immune systems and have increased gene expression as compared to other allogeneic MSCs.